Algebra for Symbolic Computation - Mach, Antonio (UNITEXT, 2012)
This book deals with several topics in algebra useful for computer science applications and the symbolic treatment of algebraic problems, pointing out and discussing their algorithmic nature. The topics covered range from classical results such as the Euclidean algorithm, the Chinese remainder theorem, and polynomial interpolation, to p-adic expansions of rational and algebraic numbers and rational functions, to reach the problem of the polynomial factorisation, especially via Berlekamp's method, and the discrete Fourier transform. Basic algebra concepts are revised in a form suited for implementation on a computer algebra system. 0